Analisis Kesulitan Pemahaman Siswa pada Pembelajaran Matematika Materi Persamaan dan Pertidaksamaan Linear Satu Variabel - Wahyuningsih, Baiq Yuni (MASALIQ, 2022)
This study tries to present various kinds of students' understanding difficulties and problems that often arise in learning One Variable Linear Equations and One Variable Linear Inequality. The focus of this research is to find and analyze students' difficulties in understanding PLSV and PTLSV materials. The research method used is qualitative research methods. The data collection technique used is the method of observation, tests and interviews. This research procedure consists of three stages, namely the preparation stage, the implementation stage and the analysis stage. The results of the study indicate several problems that occur when learning PLSV material, namely: 1) Teachers often start PLSV material by directly providing a formal definition or mathematical definition, 2) After the concept of definition is embedded, there are still students who are confused by the definition because they cannot to explain the definition back verbally, 3) The teacher forgets to explain about the elements or parts of a linear equation of one variable, 4) Students do not understand what is meant by the word completion and 5) The teacher gives examples of questions about linear equations with one variable that are not coherent difficulty level. Furthermore, the problems that occur when learning the PTLSV material, namely: 1) Students do not understand that the following three inequalities are equivalent and 2) Students do not understand the meaning and notation/writing of the final results obtained.